2015
DOI: 10.1007/s12192-015-0604-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined HSP90 and kinase inhibitor therapy: Insights from The Cancer Genome Atlas

Abstract: The merging of knowledge from genomics, cellular signal transduction and molecular evolution is producing new paradigms of cancer analysis. Protein kinases have long been understood to initiate and promote malignant cell growth and targeting kinases to fight cancer has been a major strategy within the pharmaceutical industry for over two decades. Despite the initial success of kinase inhibitors (KIs), the ability of cancer to evolve resistance and reprogram oncogenic signaling networks has reduced the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 145 publications
(155 reference statements)
0
23
0
1
Order By: Relevance
“…(10) Within this conceptual framework, attention has recently been drawn to combined targeting of oncogenic kinases through HSP90 inhibition and catalytic blockade, a two-hit strategy aimed at integrating the functional inhibition of the target kinase with its proteolytic destruction. (11) Herein, we report that three FFs, previously identified in ICC, are HSP90 clients and as such undergo rapid degradation in cells subjected to HSP90 inhibition. Furthermore, we show that FF targeting by BGJ398 in combination with the clinically advanced HSP90 inhibitor ganetespib (12) elicits superior suppression of FF oncogenic signaling in cultured cells and FF-driven NIH3T3 tumor allografts.…”
Section: Hsp90 Inhibition Drives Degradation Of Fgfr2 Fusion Proteinsmentioning
confidence: 87%
See 1 more Smart Citation
“…(10) Within this conceptual framework, attention has recently been drawn to combined targeting of oncogenic kinases through HSP90 inhibition and catalytic blockade, a two-hit strategy aimed at integrating the functional inhibition of the target kinase with its proteolytic destruction. (11) Herein, we report that three FFs, previously identified in ICC, are HSP90 clients and as such undergo rapid degradation in cells subjected to HSP90 inhibition. Furthermore, we show that FF targeting by BGJ398 in combination with the clinically advanced HSP90 inhibitor ganetespib (12) elicits superior suppression of FF oncogenic signaling in cultured cells and FF-driven NIH3T3 tumor allografts.…”
Section: Hsp90 Inhibition Drives Degradation Of Fgfr2 Fusion Proteinsmentioning
confidence: 87%
“…This notion has provided the rationale underpinning the use of pharmacological inhibitors of HSP90 (HSP90i) for therapeutic targeting of oncogenic kinases . Within this conceptual framework, attention has recently been drawn to combined targeting of oncogenic kinases through HSP90 inhibition and catalytic blockade, a two‐hit strategy aimed at integrating the functional inhibition of the target kinase with its proteolytic destruction …”
mentioning
confidence: 99%
“…Pada sel kanker paru-paru, HSP90 berperan dalam stabilisasi protein kinase seperti reseptor EFG, BRAF, HER2, dan ALK (Sang et al, 2013). Gambar 5 menunjukkan bagaimana HSP90 dapat membantu pertumbuhan sel kanker dengan beberapa cara seperti Signifikansi peranan HSP90 dalam pelipatan protein dan stabilisasinya menjadi penelaahan banyak penelitian pada tahun-tahun belakangan ini (Prince et al, 2015). Apalagi peranan HSP90 hampir mendominasi diseluruh tipe protein regulator (Hong et al, 2013).…”
Section: Kankerunclassified
“…Recent insights from the Cancer Genome Atlas revealed that multiple malignancies overexpress or possess mutant kinases that depend on the HSP90–chaperone complex. 5 HSP90 has been shown to stabilize various signaling molecules, such as PI3K and AKT proteins, thus inhibiting cellular apoptosis in cancerous cells ( Figure 1 ). 6 It also appears that HSP90 can act as a “protector” of unstable protein by-products of DNA mutations, such as v-SRC and mutant forms of p53.…”
Section: Introductionmentioning
confidence: 99%